The Effect of Sterility Values and Retort Temperatures on the Change of Physical and Sensory Properties of a Canned Mushroom Product - Didik J. Pursito; Eko H. Purnomo; Dedi Fardiaz; Purwiyatno Hariyadi (International Journal of Food Studies)
This research aimed to study the effect of sterility values on physical quality (drained weight, brown colour index, and texture) and sensory properties of canned Agaricus bisporus mushrooms processed at different retort temperatures (115, 121, and 130 °C) and processing times (2-97 minutes). Mushrooms in brine solution media packaged in 300x407 cans were heated in industrial-scale horizontal static retorts at different retort temperatures for specific processing times to reach different F0-values. The canning process was carried out following commercial production procedures in one of the mushroom canning factories. Measurement of heat penetration into the product was carried out using a protocol established by the Institute of Thermal Process Specialists (IFTPS), and the sterility values (F0) were calculated. Our results indicated that the physical and sensory properties of canned mushrooms were not only affected by sterility value but also by the combination of temperature and time used to process the product. At the same level of sterility, a higher retort temperature (130 °C) resulted in canned mushroom with a lower browning rate, an improved texture profile (decreased hardness, increased chewiness, and shear force), a sweeter taste, and increased intensity of umami taste. However, the canning process at a temperature of 130 °C resulted in a greater reduction of the drained weight as compared to that of canning at 115 °C and 121 °C.